Facing Mortality: Exploring Existentialist Motif of Death in the Selected Novels by McCarthy, Zhadan, and Müller - Shevchenko, Iryna (Respectus Philologicus, 2024)
This study represents the first scholarly endeavour to investigate the existentialist motif of death within the works of renowned authors from the United States and Europe: Cormac McCarthy’s The Road (2006), Herta Müller’s Atemschaukel (2009), and Serhii Zhadan’s Internat (2017). Employing a multifaceted methodological approach, this research utilises close reading to identify representations of the death experience, an interpretative lens to uncover and categorise imagery, allusions, and symbols related to death, and a comparative analysis based on the point-by-point method to juxtapose the literary representations of death across the selected novels. Through this study, three distinct forms of death emerge: the cessation of life, the moral decay of humanity, and the demise of nature. This study delves into these forms, which are most prominently depicted in each novel, to provide a comprehensive understanding of the nature of death at the dawn of the 21st century. The selection of these novels is predicated on their shared thematic concerns, including survival in hostile environments and extreme experiences such as isolation, alienation, and ultimately, death.